Role-Playing: A Strategy for Practicum Preparation for Foundation Year MSW Students. Issue 2 (15th March 2019) - Fulton, A. E.; Dimitropoulos, G.; Ayala, J.; McLaughlin, A. M.; Baynton, M.; Blaug, C.; Collins, T.; Elliott, G.; Judge-Stasiak, A.; Letkemann, L.; Ragan, E.
ABSTRACT: Field practicum plays a central role in social work education by socializing social work students to the profession and facilitating the integration of theoretical knowledge with skill development. Students can be apprehensive about beginning practicum and often lack adequate formal preparation for the practicum experience. This study evaluates role-playing as a prepracticum preparatory activity for foundation year MSW students. Focus groups were conducted with student role-play participants to assess the perceived quality and effectiveness of a role-play activity designed to support practicum preparation. The article concludes with a discussion of pedagogical implications and recommendations for further research.